Effects of different promoters on the protective efficacy of recombinant Marek's disease virus type 1 expressing the VP2 gene of infectious bursal disease virus. Issue 47 (11th November 2016) - Li, Kai; Liu, Yongzhen; Liu, Changjun; Gao, Li; Zhang, Yanping; Gao, Yulong; Cui, Hongyu; Qi, Xiaole; Zhong, Li; Wang, Xiaomei
Highlights: We constructed two MDV1-based IBDV vaccines using Pec or CMV promoter. The rMDV-Pec-VP2 using Pec promoter expressed a larger amount of VP2. The rMDV-Pec-VP2 induced stronger antibody response against IBDV in chickens. The rMDV-Pec-VP2 provided full protection against vvIBDV challenge in chickens. Abstract: The vaccine efficacy of recombinant viruses can be influenced by many factors. Accordingly, the activity of promoters has been one of the major factors affecting the antigen expression and protection rate. In the present study, two recombinant Marek's disease virus type 1 (MDV1) vaccines containing the VP2 gene of infectious bursal disease virus (IBDV) under control of different promoters were generated from overlapping fosmid DNAs. The rMDV-Pec-VP2 virus containing the VP2 gene under control of the Pec promoter (CMV enhancer and chicken β-actin chimera promoter) demonstrated higher VP2 expression and stronger antibody response against IBDV in chickens than the rMDV-CMV-VP2 virus using the CMV promoter. After IBDV lethal challenge in specific-pathogen-free chickens, rMDV-Pec-VP2 provided complete protection against developing mortality, clinical signs, and the formation of bursal lesions, which was better than that provided by rMDV-CMV-VP2. Our findings indicate that the protective efficacy of the recombinant MDV1 vaccine against IBDV highly correlates with VP2 expression. This recombinant MDV1 vaccine expressing VP2 could have significant potential as a bivalent vaccine against both virulent IBDV and MDV infections in chickens.